Hsa_circ_0092355 Accelerates Papillary Thyroid Cancer Progression by Regulating the miR-543/PDE5A Pathway - Sun, Zhijun; Zhang, Min; Ye, Yangmei; Yang, Leilei (Hormone and Metabolic Research, 2024)
CircRNAs have been found to participate in the progression of various tumors. In the present study, we aimed to clarify the role of hsa_circ_0092355 in papillary thyroid cancer (PTC) cell development. RT-qPCR was used to determine the expression of hsa_circ_0092355, miR-543, and PDE5A. PTC cell proliferation was ascertained via a cell colony formation assay and the CCK-8 test. Western blotting was performed to examine the expression levels of PDE5A and apoptosis-associated proteins (Bcl-2 and Bax) in PTC cells. A scratch wound assay was performed to measure the migration of PTC cells. A mouse xenograft test was performed to assess the effects of hsa_circ_0092355 in vivo. RIP and dual-luciferase reporter assays confirmed the association between miR-543 and hsa_circ_0092355 or PDE5A. Associations between miR-543, hsa_circ_0092355, and PDE5A were evaluated using Pearson’s correlation coefficient. Upregulation of hsa_circ_0092355 was observed in PTC tissues. The hsa_circ_0092355 knockdown blocked the proliferation and migration of PTC cells and induced apoptosis. Moreover, hsa_circ_0092355 knockdown blocked PTC xenograft tumor growth in vivo. The miR-543 inhibitor could reverse the changes induced by hsa_circ_0092355 knockdown by hsa_circ_0092355 targeting miR-543. Furthermore, miR-543 suppresses PTC progression by downregulating PDE5A expression. Our findings suggest that the PTC tumor promoter hsa_circ_0092355 may promote carcinogenesis by controlling the miR-543/PDE5A pathway.
Keywords: hsa_circ_0092355; papillary thyroid cancer; miR-543; PDE5A